Narwhal and Jelly. 1, Super Narwhal and Jelly Jolt - Clanton, Ben, 1988- (New York, New York : Scholastic, Inc., 2018)
Join Super Narwhal and sidekick Jelly Jolt as they take on three SUPER new stories in this early graphic novel series. Happy-go-lucky Narwhal and no-nonsense Jelly find their inner superheroes in three new under-the-sea adventures. In the first story, Narwhal reveals his superhero alter-ego and enlists Jelly to help him figure out what his superpower is. Next, Narwhal uses his superpower to help a friend find his way back home. In the third story, Jelly is feeling blue and Narwhal comes to the rescue
Narwhal is really awesome -- Narwhal's pod of awesomeness -- Narwhal and the best book ever.
"A Junior Library Guild selection"--Page 4 of cover.
Keywords: Narwhal -- Juvenile fiction; Jellyfishes -- Juvenile fiction; Marine animals -- Juvenile fiction; Friendship -- Juvenile fiction; Sea stories